PENGARUH PSIKOLOGIS KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN HANDPHONE MEREK VIVO (STUDI KASUS PADA MAHASISWA PROGRAM STUDI MANAJEMEN UNIVERSITAS VICTORY SORONG) - Susana Magdalena Welly Muskita; Arce Yulita Ferdinandus; Ratna Rosmauli Pakpahan (Fakultas Ilmu Sosial dan Ilmu Politik, 2022)
The development of communication and information technology is progressing rapidly. Along with this, communication devices (mobile phones) are no longer a secondary need but have become a primary need. Mobile is not only used to communicate via telephone or SMS, but consumers want more so that the features of the handphone are increasingly diverse. Since the internet began to boom in Indonesia, the internet has become a mandatory feature and has changed its function, so it's no wonder that the cheapest mobile phones can be used for calls, SMS, and the internet. The purpose of this study is to determine and analyze the psychological influence of consumers on the decision to purchase Vivo brand mobile phones on students of the Management Study Program, Faculty of Economics and Business, Victory University, Sorong.From the results of hypothesis testing that has been done the hypothesis is accepted. The contribution of consumer psychological influence on purchasing decisions for students of the Management Study Program, Faculty of Economics and Business, Victory University, Sorong, is 17.3%. In other words, purchasing decisions can be explained or influenced by consumer psychological variables of 17.3% while the remaining 82.7% are explained or influenced by other variables not examined.The results of the t-count value of the education and training variables can be seen that the t-count value of 3.304 is smaller than the t-table value of 1.697. Thus the hypothesis is accepted, meaning that consumer psychological variables have a significant influence on students' purchasing decisions for Vivo brand mobile phones.